Bosnia and Herzegovina : Second and Third Reviews Under the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Activity and fiscal policy continue to exceed expectations, but strong bank credit growth has fuelled a sharp increase in the current account deficit. In this context, the new administrations recognize the need to establish the macroeconomic stability quickly. These actions are supported by strengthened bank regulations. The new administrations recognize the need for sweeping structural reforms if their aspirations to eventual EU membership and sustained growth are to be realized. But with unemployment high and with large aid inflows set to decline further, risks remain.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet